MEDIA COVERAGE OF ENTREPRENEUR INNOVATIONS IN NIGERIA - Sanusi, Bernice Oluwalanu; Jolapamo, Bolanle Samuel; Odion, Victor Ebenezer; Oyegoke, Nathaniel; Oluwaranti, Ojewumi (African Journal of Social and Behavioural Sciences, 2024)
This research investigates the media coverage of entrepreneurship innovations in Nigeria, aiming to provide insights into the nature, characteristics, and implications of media representations in shaping perceptions and fostering entrepreneurial growth. Utilizing secondary data sources, this paper explored the Agenda Setting Theory as the theoretical ferment and foundation that underpinned this study. This study found a notable lack of diversity and inclusivity in media representations, with certain industries, regions, and demographic groups being overrepresented, while others are marginalized. Issues of sensationalism, bias, and inaccuracies in media coverage are also identified, which can distort public perceptions and hinder the growth of a vibrant entrepreneurial ecosystem. The study therefore recommended that media organizations should strive to diversify their coverage of entrepreneurship innovations. Journalists and media professionals should also adhere to ethical reporting standards, including fact-checking, balanced reporting, and avoiding sensationalism. By addressing these challenges and implementing the suggested recommendations, stakeholders can work towards fostering a more inclusive, accurate, and constructive media environment for entrepreneurship in Nigeria.